Surgical treatment of endometriosis. Technical considerations. Our concept - Molina Navia, Lucas (2015)
The author supports the conservative surgery in the genital endometriosis. Is, however, some difficulties in practice that rarely diagnosed preoperatively is associated with injuries requiring a greater resection or is diagnosed in women above the fourth decade of life. The possibilities of conservative surgery in endometriosis are: conserving surgery generative function, resection of uterine endometriosis, ovarian and partial resection or oophorectomy unillaterales salpingectomy, etc. Menstruo conservative surgery, indicated exclusively internal endometriosis, hysterectomy with Achner fundic, partial amputations and histeromiometrectomía. Conservative surgery of endocrine function, internal endometriosis heritage, with preservation of gonads. Study the possibilities of hormone therapy as an adjunct to conservative surgery but with residual lesions, using progestin.